THE ROLE OF MOTIVATION IN HUMAN ACHIEVEMENT - Hamrokulova Jasmina Ozodovna, (TADQIQOTLAR, 2025)
Abstract Motivation is one of the most powerful psychological and spiritual forces that govern human behavior. It does not only determine the extent of one’s efforts, but also influences resilience, creativity, and overall life satisfaction. This paper explores the multifaceted  and  deeply  important  role  of  motivation  in  shaping  human  potential, arguing that it functions as the central element that connects ambition, perseverance, and  personal  growth.  By  analyzing  motivation  from  psychological,  emotional,  and spiritual perspectives, the essay highlights how cultivating strong intrinsic motivation enables  individuals  to  overcome  adversity  and  achieve  self-actualization,  fulfilling both inner and outer purposes of life.